Maximizing the combustion phenomenon with reduced emission of a compression ignition engine fulled with Dunaliella salina biodiesel and hydrogen blends - V. Hariram; R. Sathishbabu; J. Godwin John; Nandagopal Kailiappan; K. Vijayakumar; E. Sangeeth Kumar; K. Kamakshi Priya (Scientific Reports)
Abstract Energy resource sustainability has been of critical concern as a result of unlimited energy demand worldwide. In this research work, extraction of the alternate fuel for diesel (i.e., biodiesel) from the source Dunaliella salina, which is a greenish microalga with higher lipid content comparatively, is being primarily addressed. Cultivation was provided under nitrogen starvation, f/2 trace-element supplemented, nutrient medium supplemented with vitamins and CO2. Ultrasonic extraction method at 50 Hz yielded 645 ml of Dunaliella salina bio-oil in repeated batches. One stage base catalysed process of transesterification with 1:8 mol ratio of methanol to oil, 0.6% w/w NaOH catalyst, reaction temperature of 50 °C and reaction time of 120 min yielded 612 ml Dunaliella salina biodiesel in 6 batches with 94.8% efficiency in transesterification. Physio-chemical properties of the produced biodiesel were determined to be as per ASTM specifications. Additional GCMS, NMR and FTIR spectroscopic study of the derived biodiesel established its suitability for CI engine. Dunaliella salina biodiesel blend at 20% volume ratio was compared with diesel on combustion, emission and performance characteristics of Kirloskar 240 PE test engine. Additional supplementation of Hydrogen by DuSaBD20 at 3 LPM, 6 LPM and 9 LPM had pronounced impact on the engine performance with remarkable CO reduction and UBHC and a slight increase in engine NOx was observed. Additionally, the study of cost of operation on H2 induction was also investigated.